Introducing highly conductive materials into a fin for heat transfer enhancement. (January 2019) - Hajmohammadi, M.R.; Ahmadian, M.; Nourazar, S.S.
Highlights: Insertion of highly conductive materials embedded in a straight fin is proposed. The geometric shape and configuration of inserts are optimized. It is shown that the use of highly conductive insert improves heat transfer. The efficiency of the inserts strongly depends on Biot number. Abstract: The straight fin is a common choice for enhancing heat transfer in cooling of planar systems such as the electronic chips that are becoming smaller and smaller every day. However, there is still effort required to increase the heat transfer rate per unit mass of a straight fin. With this design point of view, in this paper, a novel method is proposed by using highly conductive materials embedded in a straight fin. While the amount of such high thermal conductivity materials ('inserts') is considered as a constraint, the geometric shape and configuration of inserts are optimized to reach the maximum heat transfer. The numerical results indicate that the highly conductive materials reduce the thermal resistance of the fin and therefore, enhance the heat transfer. Also, it is shown that there exists an optimal insert aspect ratio that maximizes the insert effectiveness, depending on the insert volume fraction, Biot number, thermal conductivity ratio and the fin aspect ratio. For example, for Biot = 0.1, thermal conductivity ratio = 10 and the fin aspect ratio = 0.1, heat transfer enhancement by the fin is increased about 175% by using highly conductive materials of 10% volume fraction compared with the case of absent highly conductive materials. Graphical abstract: